PENGARUH PENGGUNAAN MODEL LEARNING CYCLE 5E DAN PEMBELAJARAN KONVENSIONAL TERHADAP HASIL BELAJAR SISWA PADA MATERI LARUTAN PENYANGGA - Maharani, Nova (Journal of Technique Research (JTR), 2019)
This research aimed at figuring out to know about the effect of learning cycle 5E (engage, explore, explain, elaborate, evaluate) towards learning outcomes of buffer solution for XI IPA grade student of Islamic Senior High School (Madrasah Aliyah Negeri-MAN) Padang. The research design was true eksperimenta with Posttest-Only Control Design. The research population was the whole total of eleventh grade of science from MAN Padang which consists of six classes. The technique of the taken sample in this research was Simple Random Sampling. The chosen sample was a class with 32 student as the experimental class that was given learning cycle 5E model and a class with 36 student as the control class was given conventional learning model. Based on the results of hypothesis test using test-t obtained significance smaller than 0.05 which means that the learning cycle model 5E showed significant effect than conventional learning towards the learning outcome of students at material buffer solution of Class XI MAN Padang with an average learning outcomes obtained to that class of experiment that is 74 and grade control 56.